Pengaruh Penerapan Model Pembelajaran Search Solve Create Share (SSCS) Berbantuan Media Pembelajaran Interaktif Terhadap Kemampuan Komunikasi Matematika Siswa - Dian Lestari; Usman Mulbar (Jurnal Akademik Pendidikan Matematika, 2026)
The research question in this study is Does the implementation of Search, Solve, Create, and Share (SSCS) learning supported by interactive learning media influence students’ mathematical communication? The objective of this study is to determine the effect of implementing Search, Solve, Create, and Share (SSCS) learning supported by interactive learning media on students’ mathematical communication. This study uses a quantitative approach with a quasi-experimental method. This study was conducted during the odd semester of the 2025/2026 academic year at a junior high school in Baubau. The population in this study consisted of all eighth-grade students, comprising five classes. The sampling technique used was cluster random sampling, as it was assumed that the initial abilities of all eighth-grade classes were relatively similar. One class was selected as the experimental class, which would subsequently use the Search Solve Create Share (SSCS) learning model supported by interactive learning media, namely Class VIII.C, and one class was selected as the control class, which used the conventional learning model, namely Class VIII.B. Based on the analysis results, a t-value of 5.251 was obtained, with a significance level of 0.000 < α = 0.05. Therefore, it is concluded that the implementation of the Search Solve Create Share (SSCS) learning model supported by interactive learning media has an effect on communication skills.